2020
DOI: 10.1055/a-1283-6550
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bowel wall thickness by ultrasound as early diagnostic tool for therapeutic response in Crohn’s disease patients treated with ustekinumab

Abstract: Background Ustekinumab was approved for the treatment of patients with moderate to severe CD 2. Development of predictors for selecting patients responding to ustekinumab has to be the next step. US offers a noninvasive method with great sensitivity in detecting CD activity 11. Aim To evaluate BWT by BS as early diagnostic tool for treatment response in CD patients treated with ustekinumab at week 8. Methods This is a prospective monocentric study. Twenty-three CD patients had BS at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For instance, for TI, both 2 and 3 mm have been used as cut-offs, while 3 or 4 mm values have been considered for colonic disease [24,26,[28][29][30][31][32][33][34]99]. For CDS, some studies have attempted to semi-quantitatively approximate the degree of hypervascularisation by using the Limberg score, while other authors preferred a dichotomous approach, with present or absent CDS [10,23,32,48,78]. Considering the many available abnormal findings, the decision on which parameters to follow is difficult and requires unification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, for TI, both 2 and 3 mm have been used as cut-offs, while 3 or 4 mm values have been considered for colonic disease [24,26,[28][29][30][31][32][33][34]99]. For CDS, some studies have attempted to semi-quantitatively approximate the degree of hypervascularisation by using the Limberg score, while other authors preferred a dichotomous approach, with present or absent CDS [10,23,32,48,78]. Considering the many available abnormal findings, the decision on which parameters to follow is difficult and requires unification.…”
Section: Discussionmentioning
confidence: 99%
“…CDS is semi-quantitatively measured according to the Limberg score in five grades, from normal bowel wall with no vascular markings (grade 0) to long streaks of Doppler signal in the bowel wall extending to the mesentery (grade 4). It can also be dichotomised into two groups: normal (grades 0 and 1) and pathological CDS (≥grade 2) [23].…”
Section: Disease Activity Evaluationmentioning
confidence: 99%
“…This is in contrast with previous reported data. Hoffmann et al 28 showed that patients with clinical and serological improvement had a decrease of BWT ⩾ 1 mm 8 weeks after the beginning of UST. More recently, a sub-study from the STARDUST (Study of Treat to Target versus Routine Care Maintenance Strategies in CD Patients Treated with Ustekinumab) trial found a statistically significant agreement between BWT and endoscopic SES-CD at week 48, with a NPV ranging from 73 to 80 at the different time points.…”
Section: Discussionmentioning
confidence: 99%
“…BWT would be useful to monitor biologics-induced bowel activity improvement in CD. [ 15,28,43] There is an increase in echogenicity of the third layer of the intestinal wall (submucosal layer) that is currently thought to be an expression of submucosal brosis, whereas hypoechogenicity of the intestinal layers is related to hyperemia and edema. [44,45] Increased BWT are important components of in ammation, [ 46] and improvement lesions are generally de ned as those with improvement (> 1mm) or normalization of BWT.…”
Section: Discussionmentioning
confidence: 99%